Synthesis, Characterization and EPR Study of Some Transition Metal Complexes with N-O Donor Lewis Base of Isonozide. - Hamed, Ahmed Solaiman; Jabbar, Araf Ismael (Al-Nahrain Journal of Science, 2018)
A series of new complexes of the type [Cu(L)2]Cl2 (1), [Ni(L)Cl2].H2O(2), [Co(L)2(H2O)2]Cl2 (3), [Mn(L)2(H2O)2] (4), [Zn(L)2Cl2] (5), where L is N-(phthalimidyl) isonicotinamide have been synthesized and characterized by magnetic moment, molar conductivity UV, and (FT-IR) and some of them were characterized by EPR spectroscopy. Ligand was characterized by FT-IR, 1HNMR and 13CNMR spectroscopy. The spectroscopic data indicated that the isonazide ligand act as bidentate N,O donors and the complexes (2-5) are paramagnetic and the complex(6) diamagnetic. The optimization of their structures indicated that the geometry of complex (1) is square planar and tetrahedral for complex (2) and octahedral for complexes (3-5).